THE EFFECT OF CARBOXYLIC-ACIDS ON THE DISSOLUTION OF CALCITE IN AQUEOUS-SOLUTION .2. D-TARTARIC,I-TARTARIC AND MESO-TARTARIC ACIDS - Barwise, A; Compton, R; Unwin, P (1990)
The effects of the dianions (A2-) of d-, I- and meso-tartaric acids on the dissolution reaction which takes place between calcite and the corresponding monoanions (HA-) has been investigated: (a) by using channel-electrode shielding measurements and (b) through the characterization of the resulting dissolution etch-pit morphologies. For the d- and I-tartaric acid system, under conditions where A2- is present at a concentration of 20 × 10-3 mol dm-3, dissolution is found to be described by the following rate law: jCa2+ = 0.01 cm s-1 [HA-]0 where [HA-]0 is the concentration (mol dm-3) of HA- at the calcite/water interface and jCa2+ is in mol s-1 cm-2. This demonstrates partial inhibition of the dissolution reaction as compared to the rate of dissolution in mineral acids. This is attributed to the adsorption of A2-. The shape of the etch pits resulting from treatment of calcite with A2-/HA- was used to infer the likely adsorption sites for the dianion. In the meso-tartaric acid system, much stronger inhibition is found and the rate of dissolution is strongly dependent on the concentration of A2- present, the rate law being given by: jCa2+ = 0.04 cm s-1 [HA-]0/1 + K[A2-] where K = 1.4 × 103 dm3 mol-1. Etch-pit morphologies indicated inhibition of both the lateral dissolution and the etch-pit nucleation process at dislocations on the calcite surface.